PENGATURAN MENGENAI KEWAJIBAN NOTARIS DALAM MELEKATKAN SIDIK JARI PENGHADAP PADA MINUTA AKTA NOTARIS TERKAIT DENGAN PERUBAHAN UNDANG-UNDANG JABATAN NOTARIS - Dita Ragiliana, Rengganis; Budi Arsika, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
This paper aims to determine the obligations of a notary in client fingerprintembedding on the official document to law office amendement of notary and sanction aregiven if the notary does not perform its obligation. This paper is a normative legal researchby using statutes approach. The Amendment of Notary Act No.2 in 2014, especially inArticle 16 paragraph (1) letter c determines obligation for the notary in making a notarialminuta. The functions of reattached fingerprint in the notarial minuta is not a legal actionto determine the validity or authenticity of the minuta but only to ensure the correct identityof client. Notaries are responsible to carry out these obligations in their profession as apublic notary, otherwise they will be imposed disciplinary sanction, except in the event of adeclaration stating the reason client cannot affix signatures and fingerprints on the officialdocument.
Keywords: Notary Obligation, Client fingerprint, Official document